Awareness of Nurse Midwives’ toward Post-miscarriage Care at Bint Al-Huda Hospital in Al-Nasiriya City (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective of Study: To assessment of nurse-midwives’ knowledge and performance concerning with postabortion Care.Methodology: A cross sectional descriptive analysis of (50) nurse midwives of this category of maternitynurse midwives was conducted in separate units of the Bint Al-Huda hospital between 19 January 2020 and30 April 2020. The questionnaire’s validity and reliability was calculated through a pilot test. Due to thecondition in the nation and the governorate, the emergence of the Corona epidemic and the implementationof curfews, the questionnaire was submitted electronically and the questionnaire was completed by thenurses and midwives, data was processed using the SPSS edition (20).Results: The test showed that 22% of the test sampler replied correctly to Encourage the client to clear thetoilet, 44% replied correctly to isolation of infected patients, 20% of the study sample responded correctlyto the importance of hand washing, 35% responded correctly to Asses vaginal bleeding, 25% of the researchsample responded correctly in, In terms of emotional assistance, 30 percent responded correctly,19 percentof the research sample replied with right Test vital signs. 38 percent of them correctly replied with regardto the patient’s medical profile, 40 percent of the test group correctly replied with regard to Perineum care.
Keywords: Assessment, Nurse, Midwives’, Knowledge, Performance, Post-abortion, Care.